Cultivating the Macroalgal Holobiont: Effects of Integrated Multi-Trophic Aquaculture on the Microbiome of Ulva rigida (Chlorophyta) - Califano, Gianmaria; Kwantes, Michiel; Abreu, Maria Helena; Costa, Rodrigo; Wichard, Thomas (Frontiers in Marine Science, 2020)
Ulva is a ubiquitous macroalgal genus of commercial interest. Integrated Multi Trophic Aquaculture (IMTA) systems promise large-scale production of macroalgae due to their high productivity and environmental sustainability. Complex host-microbiome interactions play a decisive role in macroalgal development, especially in Ulva spp. due to algal growth- and morphogenesis-promoting factors released by associated bacteria. However, our current understanding of the microbial community assembly and structure in cultivated macroalgae is scant. We aimed to determine (i) to what extent IMTA settings influence the microbiome associated with U. rigida and its rearing water, (ii) to explore the dynamics of beneficial microbes to algal growth and development under IMTA and (iii) to improve current knowledge of host-microbiome interactions. We examined the diversity and taxonomic composition of the prokaryotic communities associated with wild versus IMTA-grown Ulva rigida and surrounding seawater by 16S rRNA gene amplicons. With 3141 Amplicon Sequence Variants (ASVs), the prokaryotic richness was higher in water than in association with U. rigida. Bacterial ASVs were more abundant in aquaculture water samples than water collected from the lagoon. The beta diversity analysis revealed distinct prokaryotic communities associated with Ulva collected in both aquacultures and coastal waters. Aquaculture samples (water and algae) shared 22% of ASVs, whereas natural, coastal lagoon samples only 9%. While cultivated Ulva selected 239 (8%) host-specific ASVs, wild specimens possessed more than twice host-specific ASVs (17%). Cultivated U. rigida specimens enriched the phyla Cyanobacteria, Planctomycetes, Verrucomicrobia, and Proteobacteria. Within the Gammaproteobacteria, while Glaciecola mostly dominated the microbiome in cultivated algae, the genus Granulosicoccus characterized both Ulva microbiomes. In both wild and IMTA settings, the phylum Bacteroidetes was more abundant in the bacterioplankton than in association with U. rigida. However, we observed that the Saprospiraceae family within this phylum was barely present in lagoon water but very abundant in aquaculture water. Aquacultures promoted the presence of known morphogenesis-inducing bacteria in water samples. Our study suggests that IMTA significantly shaped the structure and composition of the microbial community of the rearing water and cultivated U. rigida. Detailed analysis revealed the presence of previously undetected taxa associated with Ulva, possessing potentially unknown functional traits.